2015
DOI: 10.14411/eje.2015.043
|View full text |Cite
|
Sign up to set email alerts
|

Aphis pomi and Aphis spiraecola (Hemiptera: Sternorrhyncha: Aphididae) in Europe - new information on their distribution, molecular and morphological peculiarities

Abstract: Abstract. Aphid species Aphis pomi (de Geer, 1773) is oligophagous on pomoideous host plants, whilst Aphis spiraecola Patch, 1914 is a polyphagous species alternating between Spiraea spp., its primary host, and a wide variety of secondary hosts, also including pomoideous species. Despite the biological distinction, these species are difficult to separate using their morphological characters. Partial sequences of mitochondrial COI and nuclear EF-1α genes were analyzed for samples from Central and Eastern Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Detailed studies of Lithuanian populations of Aphis pomi (RAKAUSKAS & RUPAIS 1983) showed their biological and ecological characters to be similar to those summarized by BLACKMAN & EASTOP (2000). On the molecular level, sampled Lithuanian populations appeared identical in their partial nuclear EF-1α gene sequences: most of the samples had the predominant European haplotype of the mitochondrial COI gene (RAKAUSKAS et al 2015a). Molecular data also confirmed the existence of A. spiraecola in Lithuania.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Detailed studies of Lithuanian populations of Aphis pomi (RAKAUSKAS & RUPAIS 1983) showed their biological and ecological characters to be similar to those summarized by BLACKMAN & EASTOP (2000). On the molecular level, sampled Lithuanian populations appeared identical in their partial nuclear EF-1α gene sequences: most of the samples had the predominant European haplotype of the mitochondrial COI gene (RAKAUSKAS et al 2015a). Molecular data also confirmed the existence of A. spiraecola in Lithuania.…”
Section: Resultsmentioning
confidence: 61%
“…Most of the Lithuanian samples of this species had the common and widely distributed (Europe, Turkey, China) haplotypes of the mitochondrial COI and nuclear EF-1α genes. The length of the ultimate rostral segment appeared to be the most reliable morphological character for discriminating between A. pomi and A. spiraecola in Lithuania, enabling 100% correct identification of the former (n = 143) and 91.5% of the latter (n = 94) species in the samples used for the molecular analysis (RAKAUSKAS et al 2015a). The coexistence between these two Aphis LINNAEUS, 1758 species is challenging for pest aphid management practice, because both species are similar in their morphology but differ in their ecological features and resistance to pesticides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of A. spiraecola is uncertain, although it most likely originated in East Asia (Blackman & Eastop 1984), and, as an invasive species, it has become an important pest of citrus and apple orchards all over the world (Blackman & Eastop 1984;Pfeiffer et al 1989;Rakauskas et al 2015). In Europe, A. spiraecola was reported in the early 1990's as a new https://doi.org/10.17221/108/2020-PPS widespread pest of the citrus growing areas of the Mediterranean region (Katsoyannos et al 1997;Cambra et al 2000;Kavallieratos et al 2007).…”
mentioning
confidence: 99%
“…In the following decade, the species was recorded from apple orchards in Central Europe: in Germany in 2000 (Litterst & Thieme 2001), in Hungary in 2004 (Mezei & Kerekes 2006), and in Bulgaria and Serbia in 2007 (Andreev et al 2007;Petrović-Obradović et al 2009). In the recent years, A. spiraecola reached the Baltic region as well (Rakauskas et al 2015). In the case of the United Kingdom, although A. spiraecola was recorded on an imported Yukka rooted stem consignment (Furk 1979) and on Cotoneaster shrubs in London (Martin 1996), there has not been any evidence of its constant presence (CABI 2020).…”
mentioning
confidence: 99%